2022
DOI: 10.1186/s12967-022-03369-9
|View full text |Cite
|
Sign up to set email alerts
|

XGBoost-based and tumor-immune characterized gene signature for the prediction of metastatic status in breast cancer

Abstract: Background For a long time, breast cancer has been a leading cancer diagnosed in women worldwide, and approximately 90% of cancer-related deaths are caused by metastasis. For this reason, finding new biomarkers related to metastasis is an urgent task to predict the metastatic status of breast cancer and provide new therapeutic targets. Methods In this research, an efficient model of eXtreme Gradient Boosting (XGBoost) optimized by a grid search alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…Logistic regression is the traditional method of predicting disease, and a Nomogram is a graph that lists the level of risk for each metric. In the past decade, the nomogram has been accepted as a reliable method for predicting tumor prognosis [9] . It has been applied to the prognosis prediction of many cancers, including gastric cancer, breast cancer, testicular cancer, etc [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Logistic regression is the traditional method of predicting disease, and a Nomogram is a graph that lists the level of risk for each metric. In the past decade, the nomogram has been accepted as a reliable method for predicting tumor prognosis [9] . It has been applied to the prognosis prediction of many cancers, including gastric cancer, breast cancer, testicular cancer, etc [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Using weighted gene co-expression network analysis, Wang et al (2020) identified six hub genes associated with IA rupture, which tended to enrich in one pathway. In addition, the gene with the highest ranking for classification importance was not necessarily the one with the greatest fold change and vice versa ( Li et al, 2022 ). The feature selection algorithm had the benefit over conventional statistical methods in this regard, favoring the selection of biomarkers that could be used to distinguish between IAs that had ruptured and those that had not.…”
Section: Discussionmentioning
confidence: 99%
“…IL32 is a pro-inflammatory cytokine that is highly expressed in malignant cells and can promote their invasion and metastasis in a variety of cancer types [37][38][39]. TMEM64 is a regulator of Wnt/β-catenin signaling pathway, which was found to be associated with metastasis in prostate and breast cancers [40,41].…”
Section: Discussionmentioning
confidence: 99%